DAF‐19/RFX controls ciliogenesis and influences oxygen‐induced social behaviors in Pristionchus pacificus. Issue 6 (26th September 2018) - Moreno, Eduardo; Lenuzzi, Maša; Rödelsperger, Christian; Prabh, Neel; Witte, Hanh; Roeseler, Waltraud; Riebesell, Metta; Sommer, Ralf J.
Abstract : Cilia are complex organelles involved in sensory perception and motility with intraflagellar transport (IFT) proteins being essential for cilia assembly and function, but little is known about cilia in an evo‐devo context. For example, recent comparisons revealed conservation and divergence of IFT components in the regulation of social feeding behaviors between the nematodes Caenorhabditis elegans and Pristionchus pacificus . Here, we focus on the P. pacificus RFX transcription factor daf‐19, the master regulator of ciliogenesis in C. elegans . Two CRISPR/Cas9‐induced Ppa‐daf‐19 mutants lack ciliary structures in amphid neurons and display chemosensory defects. In contrast to IFT mutants, Ppa‐daf‐19 mutants do not exhibit social behavior. However, they show weak locomotive responses to shifts in oxygen concentration, suggesting partial impairment in sensing or responding to oxygen. To identify targets of Ppa‐daf‐19 regulation we compared the transcriptomes of Ppa‐daf‐19 and wild‐type animals and performed a bioinformatic search for the X‐box RFX binding‐site across the genome. The regulatory network of Ppa ‐DAF‐19 involves IFT genes but also many taxonomically restricted genes. We identified a conserved X‐box motif as the putative binding site, which was validated for the Ppa ‐ dyf‐1 gene. Thus, Ppa ‐DAF‐19 controls ciliogenesis, influences oxygen‐induced behaviors and displays a high turnover of its regulatory network.